2022
DOI: 10.3847/1538-4357/ac5b60
|View full text |Cite
|
Sign up to set email alerts
|

SOAR/Goodman Spectroscopic Assessment of Candidate Counterparts of the LIGO/Virgo Event GW190814*

Abstract: On 2019 August 14 at 21:10:39 UTC, the LIGO/Virgo Collaboration (LVC) detected a possible neutron star–black hole merger (NSBH), the first ever identified. An extensive search for an optical counterpart of this event, designated GW190814, was undertaken using the Dark Energy Camera on the 4 m Victor M. Blanco Telescope at the Cerro Tololo Inter-American Observatory. Target of Opportunity interrupts were issued on eight separate nights to observe 11 candidates using the 4.1 m Southern Astrophysical Research (SO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The Rubin time-domain ecosystem of data, brokers, and routine spectroscopic follow-up is likely to minimize positives, though perhaps not until after O4. As discussed in Morgan et al (2020), Garcia et al (2020), andTucker et al (2022), the need for coordination with spectroscopic telescopes is vital in identifying the true counterpart. Given that there has only been one confirmed optical counterpart, there is uncertainty in the expected light curve from photometric data.…”
Section: Blanco/decam and Rubin Lsstmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rubin time-domain ecosystem of data, brokers, and routine spectroscopic follow-up is likely to minimize positives, though perhaps not until after O4. As discussed in Morgan et al (2020), Garcia et al (2020), andTucker et al (2022), the need for coordination with spectroscopic telescopes is vital in identifying the true counterpart. Given that there has only been one confirmed optical counterpart, there is uncertainty in the expected light curve from photometric data.…”
Section: Blanco/decam and Rubin Lsstmentioning
confidence: 99%
“…The third LIGO/Virgo/KAGRA (LVK) collaboration observing run (O3) resulted in over 60 new events (see the third Gravitational-wave Transient Catalog, GWTC; LIGO Scientific Collaboration et al 2023). One GW event originated from a BNS merger, and two high-confidence events originated from NS-BH coalescences (Abbott et al 2021), but no EM counterparts were confirmed from any event despite extensive follow-up campaigns (e.g., Andreoni et al 2019Andreoni et al , 2020Goldstein et al 2019;Garcia et al 2020;Morgan et al 2020;Kilpatrick et al 2021;Oates et al 2021;Tucker et al 2022). One study (Graham et al 2020) proposed an AGN counterpart to the binary black hole merger GW190521, but the association with the GW event cannot be made with confidence (Ashton et al 2021;Palmese et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…At of the end of O3, several GW detections of NS-BH merger candidates have been reported (Abbott et al 2021;The LIGO Scientific Collaboration et al 2021a), but no EM counterpart to an NS-BH merger was found (e.g., Anand et al 2021;Dichiara et al 2021; for the most robust NS-BH GW detections). Extensive follow-up was also performed for the peculiar source GW190814 (Dobie et al 2019;Gomez et al 2019;Ackley et al 2020;Andreoni et al 2020;Morgan et al 2020;Thakur et al 2020;Vieira et al 2020;Watson et al 2020;Alexander et al 2021;de Wet et al 2021;Kilpatrick et al 2021;Dobie et al 2022;Tucker et al 2022). However, the nature of the secondary component of GW190814 is unclear, as it can be either the lightest black hole or the heaviest NS ever discovered in a double compactobject system (Abbott et al 2020c).…”
Section: The Rubin Quest For the Unknown: Em Counterparts To Ns-bh Me...mentioning
confidence: 99%
“…The fifth (GW190425) was confirmed as a confident BNS merger (Abbott et al 2020). Despite copious follow-up, no EM transients were confirmed as GW counterparts (Andreoni et al 2019(Andreoni et al , 2020Coughlin et al 2019;Dobie et al 2019Dobie et al , 2022Goldstein et al 2019;Gomez et al 2019;Hosseinzadeh et al 2019;Lundquist et al 2019;Antier et al 2020aAntier et al , 2020bAckley et al 2020;Garcia et al 2020;Gompertz et al 2020;Kasliwal et al 2020;Morgan et al 2020;Pozanenko et al 2020;Thakur et al 2020;Vieira et al 2020;Watson et al 2020;Alexander et al 2021;Anand et al 2021;Becerra et al 2021;Bhakta et al 2021;Chang et al 2021;de Wet et al 2021;Dichiara et al 2021;Kilpatrick et al 2021;Oates et al 2021;Ohgami et al 2021;Paterson et al 2021;de Jaeger et al 2022;Tucker et al 2022; see Rastinejad et al 2022b for a comprehensive discussion).…”
Section: Introductionmentioning
confidence: 99%